2018
DOI: 10.1105/tpc.18.00011
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Systemic Nitrogen Signaling in Arabidopsis Roots Involve trans-Zeatin in Shoots

Abstract: Plants face temporal and spatial variation in nitrogen (N) availability. This includes heterogeneity in soil nitrate (NO) content. To overcome these constraints, plants modify their gene expression and physiological processes to optimize N acquisition. This plasticity relies on a complex long-distance root-shoot-root signaling network that remains poorly understood. We previously showed that cytokinin (CK) biosynthesis is required to trigger systemic N signaling. Here, we performed split-root experiments and u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
150
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(161 citation statements)
references
References 72 publications
11
150
0
Order By: Relevance
“…Plants guide appropriate root foraging activities by integrating, at an organismal level, information concerning external availability of and internal demand for N (Gent & Forde, 2017;Poitout et al, 2018). The plant hormone cytokinin was shown to be important in this context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants guide appropriate root foraging activities by integrating, at an organismal level, information concerning external availability of and internal demand for N (Gent & Forde, 2017;Poitout et al, 2018). The plant hormone cytokinin was shown to be important in this context.…”
Section: Introductionmentioning
confidence: 99%
“…The plant hormone cytokinin was shown to be important in this context. Cytokinins, long recognized as local and systemic messengers of soil N availability and the plant N status (Kiba & Krapp, 2016;Osugi et al, 2017;Landrein et al, 2018), were recently shown to mediate a shoot-to-root N demand signalling that shapes the plant responses to heterogeneous soil nitrate conditions (Ruffel et al, 2016;Poitout et al, 2018). Cytokinins are also known to locally and systemically regulate root nodule formation, hence aiding in the symbiotic N 2 acquisition (Cooper & Long, 1994;Murray et al, 2007;Frugier et al, 2008;Sasaki et al, 2014;Gamas et al, 2017;Reid et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: Arabidopsis thaliana; dual-affinity nitrate transporter; nitrate uptake; NRT1.1; NRT2.1; NRT2.2 Nitrate (NO À 3 ) is the major form of nitrogen absorbed by the roots of most terrestrial plants [1]. It not only acts an N source for growth and development but has also been proposed to act as a signal regulating several physiological processes, such as seed germination [2], root development [3], and flowering time [4,5], among others [6][7][8][9]. To better adapt to fluctuating nitrate availability, plants have evolved two uptake systems: one operating at low external nitrate concentrations, where nitrate is absorbed by high-affinity transport systems (HATS), the other acting at high nitrate concentrations through low-affinity transport systems (LATS) [10][11][12].…”
mentioning
confidence: 99%
“…It has been recently demonstrated that systemic signalling occurring via root produced cytokinins also plays an important role in preferential root foraging under heterogeneous nitrate conditions. Based on the observation that triple ck biosynthesis mutants show hardly an increase in LR length on the high nitrate side compared to homogeneous nitrate conditions, this CK based signalling system was interpreted as a demand signal (Ruffel et al, 2011;Poitout et al, 2018). Still, root CK production correlates with local root nitrate levels, suggesting that it is more natural for CK to be a supply signal (Takei et al, 2002).…”
Section: Role Of Systemic Ck Signallingmentioning
confidence: 99%
“…Thus, upregulation of NRT2.1 appears to also stimulate lateral root growth in the presence of nitrate through auxin, but via a different, less direct mechanism. Finally, an important role for systemic CK signaling in preferential nitrate foraging has been recently uncovered (Ruffel et al, 2011;Poitout et al, 2018). Plant roots were found to produce CK in a nitrate dependent manner, with this CK subsequently being transported to the shoot, where it controls the expression of a large number of genes as well as impacts preferential root foraging.…”
Section: Introductionmentioning
confidence: 99%